Vitamin D inhibits pro-inflammatory cytokines in the airways of cystic fibrosis patients infected by Pseudomonas aeruginosa- pilot study - M. Olszowiec-Chlebna; A. Koniarek-Maniecka; A. Brzozowska; A. Błauż; B. Rychlik; I. Stelmach (BMC, 2019)
Abstract Background Vitamin D plays an important role in inflammatory responses after antigen exposure. Interleukin-23 (Il-23) promotes Il-17-dependent inflammation during Pseudomonas aeruginosa (P. aeruginosa) pulmonary infection. We aimed to compare the ability of calcitriol and cholecalciferol to modulate the inflammatory response of the CF airways infected with P. aeruginosa. Methods This was a randomized, placebo-controlled, double-blind, cross-over trial. Twenty-three patients with CF (aged 6-19), chronically infected by P. aeruginosa were randomly assigned to: calcitriol group receiving 1,25(OH)2D 0,5 mcg daily or cholecalciferol group receiving cholecalciferol 1000 IU daily for three months. The levels of Il-23 and Il-17A in the exhaled breath concentrate (EBC) were measured. Calcium-phosphorus balance was also evaluated (serum concentration of calcium, phosphorus, 25OHD, parathormone (PTH) and calcium/creatinine ratio in urine). Data were analyzed using means of Stata/Special Edition, release 14.2. A level of P < 0.05 was considered statistically significant. Results The level of Il-17A in EBC significantly decreased in calcitriol group from 0,475 pg/mL (± SD 0,515 pg/mL) to 0,384 pg/mL (± SD 0,429 pg/mL) (p = 0,008); there was no change in cholecalciferol group (p = 0,074). The level of Il-23 in EBC did not significantly change in calcitriol group (p = 0,086); there was significant decrease in cholecalciferol group from 8,90 pg/mL (± SD 4,07 pg/mL) to 7,33 pg/mL (± SD 3,88 pg/mL) (p = 0,001). In calcitriol group serum phosphorus and PTH significantly decreased (p = 0,021 and p = 0,019 respectively), the concentration of calcium significantly increased (p = 0,001); there were no changes in cholecalciferol group. Conclusions Both analogs of vitamin D revealed their anti-inflammatory effect and reduced the level of Il-17A and Il-23 in the airway of CF patients with chronic P. aeruginosa infection. We observed improvement in calcium-phosphorus metabolism after supplementation with calcitriol, without adverse effects. It is recommended to use vitamin D in CF patients.